2009
DOI: 10.2337/diaspect.22.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels Among Participants in the Robert Wood Johnson Foundation Diabetes Initiative

Abstract: Objective. The purposes of this study were to describe physical activity habits of individuals with type 2 diabetes participating in a selfmanagement initiative conducted in real-world settings that was sponsored by the Robert Wood Johnson Foundation (RWJF); to assess changes in physical activity over time; and to identify factors associated with physical activity levels.Research design and methods. Clinical and community-based programs participating in the RWJF-funded Diabetes Initiative implemented comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We identified 308 studies through searching the database. Eleven studies met the inclusion criteria and were included for the systematic review (8,18,(20)(21)(22)(23)(24)(25)(26)(27)(28). The interrater reliability between the first and second coder, represented by the Cohen's k coefficient, was 0.57, indicating moderate agreement (29).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 308 studies through searching the database. Eleven studies met the inclusion criteria and were included for the systematic review (8,18,(20)(21)(22)(23)(24)(25)(26)(27)(28). The interrater reliability between the first and second coder, represented by the Cohen's k coefficient, was 0.57, indicating moderate agreement (29).…”
Section: Search Resultsmentioning
confidence: 99%
“…However, the consistent pattern of effects of self-efficacy on selfmanagement still provided strong evidence of the relationship and important information for future research and practice. Second, eight studies reported psychometric properties of study measures for their samples (8,18,20,21,(23)(24)(25)(26); the remaining three studies, although using validated scales, failed to report the reliability and validity specific to their samples (22,27,28), rendering their findings less convincing. Third, in terms of confounders, all included studies controlled for demographic variables, eight controlled for duration of diabetes, and six controlled for the comorbid conditions.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Study Findings)Physical Activity and Its Impact on Type 2 DiabetesPhysical activity plays a crucial role in the management and prevention of Type 2 Diabetes Mellitus. Several sources indicate that physical activity is an essential strategy for the management of Type 2 Diabetes Mellitus(Yazid & Busthomy, 2022).Similarly, some other researchers have found that interventions using the types of behavioral approaches that these diabetes self-management programs used have led people with Type 2 Diabetes Mellitus to increase their physical activity levels, although not to the extent recommended by public health guidelines(Williams-Piehota et al, 2009). A scoping review was conducted to explore the challenges and opportunities for physical activityinterventions in Type 2 Diabetes Mellitus sufferers in Indigenous areas throughout the world pISSN: 2654-2927 eISSN: 2656-4653 http://ejurnal.ung.ac.id/index.php/jnj | 72 and found that there is a lack of high-quality intervention studies in this area (MacMillan et al, 2014).…”
mentioning
confidence: 99%